The Application Concentration Addition of Skim Milk to Soy Milk Kefir - Mandang, Filan O.; Dien, Henny; Yelnetty, Afriza (Pascasarjana Unsrat, 2016)
Soy milk is a product processed soybean extract that resembles cow’s milk. High protein content makes soy milk as highly nutritious vegetable milk. But the beany flavor of the resulting lead soy milk consumption levels are relatively low. One way of improving the quality of soy milk with a probiotic drink that process into soy milk kefir. The purpose of this study to determine the effect of the concentration of skim milk to soy milk kefir quality, namely in terms of the physical and chemical properties, microbiological and organoleptic. The study was conducted in two stages: determining the length of fermentation and then proceed with the manufacture of soy milk with the addition of different concentrations of skim milk of four treatments that control, the addition of skim milk concentration 0%, 4% and 8%. This research using completely randomized design (CRD). The result showed the addition of skim milk concentration effect on total of bacteria acid lactic (BAL), total yeast, colour, and flavor of soy milk kefir. The addition of skim milk concentration causes an increase in total BAL, total yeast and pH. For organoleptic show that the colour and flavor of soy milk kefir with a concentration of 8% skim milk is preferred compared with the three other treatments. Keywords: soy milk, kefir, skim milk, organoleptic